Eden Close : novel - Shreve, Anita (London Abacus, 2000)
Front Cover -- Front Matter -- Praise for Eden Close -- Half Title -- Also by Anita Shreve -- Title -- Copyright -- Dedication -- 1 -- 2 -- 3 -- 4 -- 5 -- 6 -- Back Matter -- Other Novels by Anita Shreve
A compelling tale of edgy, small-town emotions, lingering obsession, and romantic salvation. Andrew, after many years, returns to his hometown to attend his mother's funeral. Planning to remain only a few days, he is drawn into the tragic legacy of his childhood friend and beautiful girl next door, Eden Close. An adopted child, Eden had learned to avoid the mother who did not want her and to please the father who did. She also aimed to please Andrew and his friends, first by being one of the boys and later by seducing them. Then one hot night, Andrew was awakened by gunshots and piercing screams from the next farm: Mr. Close had been killed and Eden blinded. Now, seventeen years later, Andrew begins to uncover the grisly story - to unravel the layers of thwarted love between the husband, wife, and tormented girl. And as the truth about Eden's past comes to light, so too does Andrew's strange and binding attachment to her reveal itself
Keywords: Detective and mystery stories; Friendship -- Fiction